Analysis of Interpersonal Communication Patterns Between Mudir and Ustaz in Boarding School Management: A Case Study in Darul Hadith Palembang - Vicky Chandra; K.A. Bukhori; Henny Yusalia; Indriyani Indriyani; Mohd Hisyamuddin bin Mohd Yussof (JURNAL AT-TURAS, 2025)
Islamic boarding schools (pesantren) play a significant role in character education and religious learning in Indonesia. Effective management relies on strong leadership and interpersonal communication between administrators and educators. Communication patterns influence decision-making, conflict resolution, and overall institutional effectiveness. In pesantren, the relationship between mudir (leader) and ustaz (teachers) is crucial for maintaining discipline and achieving educational goals. This study aims to describe the pattern of interpersonal communication between mudir and ustaz in Pondok Pesantren Darul Hadits Palembang and analyse its influence on the management of the pesantren. Using a sequential mixed method, the study started with a quantitative approach to identify communication patterns, followed by qualitative analysis for deepening. Results showed the dominance of open (64%) and assertive (63%) communication patterns, reflecting transparency, assertiveness, and clarity of instructions from the mudir. The communication structure is hierarchical, with mudir as the main authority. The implications of these findings suggest that open and assertive communication patterns, supported by the mulazamah-based education system, strengthen interpersonal relationships and the effectiveness of pesantren management